Technique for Latex Injection and Reuse of Human Heads Preserved in Formaldehyde - Dolci, Ricardo L.L.; Burchianti, Lívia Castellari; Todeschini, Alexandre Bossi; Lopes, Andre Fanhani; Barros, Mirna Duarte; Santos, Américo Rubens Leite dos; Lazarini, Paulo Roberto (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Understanding the anatomy of the skull base is paramount for every skull base surgeon, particularly in light of the expanded endoscopic endonasal approaches, and of the refined surgical technique used in both medial and lateral approaches. A comprehensive knowledge of anatomy is the cornerstone for a safe surgery, maximizing resection and minimizing complications. The best study method is the careful dissection of fresh human cadaveric heads in a well-equipped anatomy laboratory. In this study, we describe our protocol for preparing cadaveric specimens without vascular injection, which had been preserved in a formaldehyde solution after treating them with a dimethyldioctadecylammonium chloride/distearyl dimethyl ammonium chloride solution (commercial fabric softener) and injecting the vascular system with latex.Method Six cadaveric specimens underwent our treatment and subsequent injection of the vascular system and dissection.Results All specimens showed a good penetration of the latex and a clear improvement of the malleability of the tissues was noticed. The authors agree that this technique improved the quality of the head and facilitated studying.Conclusion We consider this an effective treatment with latex, reaching small caliber vessels, and a greater malleability and flexibility of tissues, allowing better dissections, and greater anatomical exposure, making them suitable for skull base training, study, and research.
Keywords: cadaveric specimen; dissection; endoscopy; latex injection; neurosurgery; otolaryngology; skull base